2020
DOI: 10.1180/clm.2020.14
|View full text |Cite
|
Sign up to set email alerts
|

Potential use of Kebilian clay reserves(southern Tunisia)for the production of geopolymer materials

Abstract: The aim of this study was to help drive the Tunisian construction industry towards a more sustainable approach given the existence of abundant local raw material deposits that could be exploited for the production of low-CO2 binders. Various clay sediments from the Kebili region (southern Tunisia) were characterized by chemical analysis, X-ray diffraction, thermal analysis and geotechnical tests to determine their suitability for the preparation of geopolymer binders. The clays consist of illite and kaolinite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 61 publications
(61 reference statements)
1
1
0
Order By: Relevance
“…Illite clay has been valorized as a substitute of metakaolin in the synthesis of new geopolymeric materials and compressive strength reached 23 MPa, while hybrid system with 50 % metakaolin could reach 40 MPa [14]. Similar result was obtained by Ounissi et al which reached strength of 25 MPa at the age of 7 days [11]. Calcined illite clay chemical treatment with an 8 M NaOH solution can also lead to the formation of the zeolites and sodium aluminium silicate hydrate [15].…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…Illite clay has been valorized as a substitute of metakaolin in the synthesis of new geopolymeric materials and compressive strength reached 23 MPa, while hybrid system with 50 % metakaolin could reach 40 MPa [14]. Similar result was obtained by Ounissi et al which reached strength of 25 MPa at the age of 7 days [11]. Calcined illite clay chemical treatment with an 8 M NaOH solution can also lead to the formation of the zeolites and sodium aluminium silicate hydrate [15].…”
Section: Introductionsupporting
confidence: 71%
“…It has been reported that the red clays in Thailand have high potential to produce low-cost geopolymers [10]. Illite clay calcining temperature varies between 600-900 °C while the most cases select 800 °C [11], [12]. Some reports state that it has not yet been possible to synthesize meta-illite-smectite-based geopolymers of high strength (>20 MPa) without the addition of ____________________________________________________________________________ 2021 / cement additives [13].…”
Section: Introductionmentioning
confidence: 99%